Swedish journalist 2005 - Asp, Kent (University of Gothenburg, 2014)
The Swedish journalist survey is conducted at the Dept of Journalism, Media and Communication (JMG) at the University of Gothenburg. The questionnaire is submitted to 2,000 randomly selected journalists from all over Sweden.

The purpose of the study is to investigate how Swedish journalists perceive themselves and society, their professional role and work situation, the problems related to their code of professional ethics and the developments in the media sector.

Journalist´05 was JMG’s fifth survey. The first one was conducted in 1989 and the results were for example presented in the book Svenska Journalister - ett grupporträtt, which was published in connection with the Swedish Union of Journalists’ 90th anniversary in 1991.

The Swedish media system has changed dramatically since 1989. The state’s broadcast media monopoly has been abolished, commercial radio and TV, the Internet and a number of new media have emerged, and the work methods have changed, largely as a result of new technologies becoming available.

The main purpose of the journalist surveys is to investigate in a broad perspective which changes Swedish journalists have gone through during this reformation of the Swedish media landscape. Many questions asked as part of the survey are therefore the exact same as those asked in the very first survey in 1989. The long duration of the study is unique, both nationally and internationally.

Purpose:

The purpose of the study is to investigate how Swedish journalists perceive themselves and society, their professional role and work situation, the problems related to their code of professional ethics and the developments in the media sector.

Journalist 2005 är den femte undersökningen i serien som genomförts vid Institutionen för journalistik, medier och kommunikation, Göteborgs universitet (JMG). Den första undersökningen gjordes 1989.

Under de år som gått sedan 1989 har det svenska mediesystemet förändrats i grunden. Etermediemonopolet har avskaffats, kommersiell radio och TV har vuxit fram, internet och nya medier har kommit till, arbetssätt har förändrats och påverkats av nya tekniker. Det främsta syftet med journalistundersökningarna är ge en bred belysning av vilka förändringar som ägt rum i journalistkåren under denna omdaning av det svenska medielandskapet. Många frågor i undersökningarna ställs därför på samma sätt som i den första undersökningen från 1989.

Den långa undersökningsserien är unik, även i ett internationellt perspektiv. En motsvarande undersökningsserie finns endast i USA.

Syfte:

Undersökningen syftar till att belysa hur svenska journalister ser på sig själva och samhället, sin yrkesroll, arbetssituation och medieutvecklingen.
Journalist 2005
Keywords: mass media; massmedia; occupations; yrken; professional ethics; yrkesetik; journalism; journalistik; occupational life; yrkesliv; professional associations; yrkesföreningar; journalists; journalister; Media; Media; Information society; Informationssamhället; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper